Optical absorption and electron dynamics in reduced graphene oxide-nanostructured porphyrin for active solar cell layers. (2020) - Bakour, Anass; Bajjou, Omar; Khenfouch, Mohamed; Baitoul, Mimouna; Mothudi, Bakang; Maaza, Malik; Wéry, Jany; Faulques, Eric
Abstract: This work outlines a study to gain further understanding of the interactions of two interesting materials, the reduced graphene oxide, and porphyrin nanostructured. We seek to address the changes occurring in morphological and opto-structural properties of the resultant composite material using different spectroscopies and by changing pH values. The structural analysis by X-ray diffraction suggests an enhancement of the composite structure, which is further confirmed by the scanning electron microscopy. The acidity effect on the resulting properties was investigated by preparing multiple samples with different pH values. The optical properties highlighted the photoluminescence intensities quenching in the composite for optimum pH values, which is a favourable property for inserting in energy applications. Furthermore, the study of electron-hole pair dynamics was conducted by means of Time resolved photoluminescence. Obtained results prove that the excitons exhibit a longer lifetime for the composite sample and therefore confirming the electron transfer from porphyrin nanostructured to reduced graphene.